Black Start Operation using a MMC based HVDC system. Issue 1 (August 2021) - Sudarsana Reddy, K.; Vigneshwar, R.; Tripathi, Anushka; Soundharya, S P; Kirthika Devi, V. S.
Abstract: Blackouts could occur due to various faults and in order to keep the power stations running constantly to avoid consumers losing power a backup plan is necessary. Black start is the process of restoring power to the electric power stations. The Modular Multilevel Converter (MMC) topology has been propitious technology in High Voltage DC (HVDC) system. The research in MMC technology has significantly increased. The MMC based HVDC system has many advantages when compared to the other technology based HVDC system. In this paper, Black Start Operation using a MMC Based HVDC system is proposed to provide continuous power to the load for a certain period of time within which alternative methods of power generation can be made ready. The paper also provides a mathematical model of a continuous equivalent circuit of the MMC Phase Leg. The efficiency of the proposed idea has been verified by MATLAB/Simulink Software and discussed.